INTERACTIVE WORDWALL : TEACHING WRITING TO EFL STUDENTS - Indri Natasya Winhartanti Julika; Ayu Istiana Sari; Imroatul Ma'fiyah (JEELL (Journal of English Education, Linguistics and Literature), 2025)
The objective of this study to examine the use of interactive Wordwall as a digital teaching and learning writing English Foreign Language (EFL) on descriptive at the seventh grade of a public junior high school in Central Java during the 2024/2025 academic year. This study used a Classroom Action Research (CAR) design and conducted in two cycles, each consist of planning, action, observation, and reflection. The sample of this research was 29 students from seventh grade of junior high school. The topic focused on describing public places and implemented interactive Wordwall activities, especially unjumbled sentences task. The data were collected through writing tests (pre-test, post-test 1, post-test 2), observation, and documentation. The data were analyzed used quantitative methods by comparing the average scores obtained at each stage. The findings of the study suggested the application of Wordwall significantly improved students’ writing skill on descriptive text. The average score increased from 56 in the pre-test with 27.65% of students nearly achieved the minimum completion criteria, to 73 in post-test 1 with 69%, and improved further to 80 in post-test 2 with 82.8%, surpassing the minimum completion criteria of 75. This study concludes that Wordwall can effectively improved students' writing ability through interactive teaching and learning methods based on digital learning media.